Exosomal RNAs in the development and treatment of pituitary adenomas - Chang, Mengqi; Jiang, Shenzhong; Guo, Xiaopeng; Gao, Jun; Liu, Peng; Bao, Xinjie; Feng, Ming; Wang, Renzhi (Frontiers in Endocrinology, 2023)
Exosomes are small extracellular vesicles that carry various bioactive molecules including various RNAs that modulate the activities of recipient cells. It has drawn considerable attention as means of cell communication and drug delivery. Exosome plays important role in various tumors, but it is rarely summarized in pituitary adenoma (PA). PA is the second most common primary central nervous system tumor, and its recurrence and persistent postoperative hormone hypersecretion lead to compromised quality of life. How exactly exosomes impact tumor development and hormone secretion is important for the development of this tumor diagnosis and treatment. In this review, we discuss how exosomal RNAs impact PAs and their potential as future clinical therapies. In our literature review, first, we found that exosomal microRNA hsa-miR-1180-3p is a potential early biomarker for NFPAs. Since NFPAs are typically difficult to diagnose, this is an especially important finding. Second, exosomal protein transcripts are potential invasive biomarker, such as MMP1, N-cadherin, CDK6, RHOU, INSM1, and RASSF10. Third, exosomal contents such as hsa-miR-21-5p promote distant bone formation of GHPA patients. Fourth, tumor suppressors in the exosome constitute novel therapeutic application of exosome, including long noncoding RNA (lncRNA) H19, miR-149-5p, miR-99a-3p, and miR-423-5p. This review discusses the possible mechanisms of exosome and their contents in PA and promotes the use of exosomes in both clinical diagnosis and treatment of this tumor.